Overutilization of surgical resection for benign colorectal polyps: analysis from a tertiary care center - Saade, Rayan; Tsang, Tyler; Kmeid, Michel; Miller, David; Fu, Zhiyan; Litynski, James; Young, Patrick; Anderson, Joseph C.; Lee, Hwajeong; Tadros, Micheal (Endoscopy International Open, 2021)
Background and study aims Adequate removal of precancerous polyps is an independent factor in colorectal cancer prevention. Despite advances in polypectomy techniques, there is an increasing rate of surgery for benign polyps. We assessed whether surgical resection is properly utilized for benign colorectal polyps.Patients and methods We identified 144 patients with surgical resection for benign colorectal polyps. Polyp location, size and the indication for and type of surgery were obtained. For the purposes of this analysis, we assumed that gastroenterologists should assess polyp size accurately, endoscopically resect polyps < 2 cm, and treat incompletely excised polyps on follow-up.Results A total of 118 patients (82 %) were referred to surgery without attempted endoscopic removal. In 26 (22 %) of 118, the macroscopic polyp size was < 2 cm (23 in right, 3 in the left colon) and 18 (15 %; 14 in the right, four in the left colon) were found to have had size overestimation during endoscopy. Twenty-two (15 %) of 144 underwent surgical resection for incomplete endoscopic resection of adenomas (16 in the right, 6 in the left colon); 12 (54.5 %) had a residual polyp size of < 2 cm (10 in the right colon; 2 in the left colon). In-hospital mortality was 0.7 % and morbidity was 20.1 %.Conclusions Of the patients, 41 % could have potentially avoided surgical intervention (37 polyps < 2 cm and/or size overestimations precluding endoscopic polypectomy and 22 incomplete resections). When including polyps with size ≥ 2 to < 4 cm, the percentage of patients with avoidable surgery reached 80 %. This confirms the need to develop standardized quality metrics for endoscopic polypectomies and for better overall training of endoscopists performing these procedures. Given the risks of surgery, referral to an experienced gastroenterologist should be considered as a first step.